STRATEGI GURU PAI UNTUK MENANAMKAN AKHLAK TERPUJI MELALUI BUDAYA RELIGIUS DI SMPI SUNAN AMPEL MOJOKERTO - Bariroh, Umi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This study is based on the utilization of religious culture in Sunan Ampel Kutorejo Mojokerto Islamic Middle School with the following problem formulations: 1) Forms of religious culture in Sunan Ampel Kutorejo Mojokerto Islamic Middle School 2) Strategies used by PAI teachers to instill religious culture 3) The impact of religious culture on student morals, this study is to describe these three things. To achieve this target, this study used a qualitative approach with a descriptive method of research. Methods of gathering information completed using perception procedures, interviews and documentation. The collected information is described by reducing information, introducing information and determining.The results of the study revealed that the religious culture at Islamic Middle School Sunan Ampel Kutorejo Mojokerto includes: 5S (Greetings, greetings, smiles, courtesy and courtesy), congregational prayers (dhuha, dhuhur, asr, and Friday), charity Friday, Islamic holidays, BTA, Gemajuza Juz 30, tadabbur alam . The PAI teacher's strategy in instilling commendable morals through religious culture is: (Planning, Action, exemplary, habituation, instilling discipline, creating a conducive atmosphere, integration), assessment. The impact of religious culture on student morals, explicitly: forming discipline, honesty, forming religious values, tolerance, and social care are all framed as one.